2013
DOI: 10.1088/2041-8205/779/1/l8
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF AN OUTBURST ONE YEAR PRIOR TO THE EXPLOSION OF SN 2011ht

Abstract: Using imaging from the Pan-STARRS1 survey, we identify a precursor outburst at 287 and 170 days prior to the reported explosion of the purported Type IIn supernova (SN) 2011ht. In the Pan-STARRS data, a source coincident with SN 2011ht is detected exclusively in the z P1 and y P1 -bands. An absolute magnitude of M z ≃-11.8 suggests that this was an outburst of the progenitor star. Unfiltered, archival Catalina Real Time Transient survey images also reveal a coincident source from at least 258 to 138 days befor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 44 publications
6
84
0
Order By: Relevance
“…Finally, one of the SNe IIn with the LC plateau, SN 2011ht, is found to have brightened a year before the major luminosity increase in 2011 (Fraser et al 2013). If SN 2011ht is associated with a super-AGB star, the pre-outburst could be related to the thermal pulses of He-shell burning in the super-AGB progenitor.…”
Section: Type Iin Supernovae With Lc Plateau (Type Iin-p)mentioning
confidence: 97%
“…Finally, one of the SNe IIn with the LC plateau, SN 2011ht, is found to have brightened a year before the major luminosity increase in 2011 (Fraser et al 2013). If SN 2011ht is associated with a super-AGB star, the pre-outburst could be related to the thermal pulses of He-shell burning in the super-AGB progenitor.…”
Section: Type Iin Supernovae With Lc Plateau (Type Iin-p)mentioning
confidence: 97%
“…in the UVW2 band over 40 days, peaking at a u-band magnitude of about −18. Fraser et al (2013) reported on an outburst peaking at a z-band absolute magnitude of −11.8 detected ∼9 months prior to the explosion, and with the last detection ∼4 months before the explosion. The event was detected by both PanSTARRS-1 and the Catalina Sky Survey.…”
Section: Sn 2011htmentioning
confidence: 99%
“…Recently, five SNe with candidate pre-explosion outbursts (precursors) have been detected a few months to years prior to the SN explosion: SN 2006jc (Foley et al 2007; Pastorello et al 2007), SN 2009ip (Mauerhan et al 2013a(Mauerhan et al , 2014Pastorello et al 2013Ofek et al 2013b), PTF 11qcj (Corsi et al 2014), and SN 2011ht (Fraser et al 2013). In most cases, these precursors were detected from SNe IIn, or closely related events.…”
Section: Introductionmentioning
confidence: 99%
“…Some supernova (SN) progenitors exhibit vigorous variability or possible explosive outbursts shortly (weeks to years) prior to the SN explosion (Foley et al 2007;Pastorello et al 2007;2013, Fraser et al 2013Mauerhan et al 2013;Ofek et al 2013aOfek et al , 2013bOfek et al , 2014aMargutti et al 2014). SNe showing such activity are mostly of Type IIn (and Ibn), with spectra showing a blue continuum and hydrogen Balmer (and helium) emission lines (Schlegel 1990;Filippenko 1991Filippenko , 1997Pastorello et al 2008;Kiewe et al 2012).…”
Section: Introductionmentioning
confidence: 99%